Facsimile Editions in O Castro, an Example of Recovering Historical MemoryRecovering Historical Memory: Civil War, Repression and Exile in Ediciós do Castro - Portela Yáñez, María Rosario (Madrygal. Revista de Estudios Gallegos, 2015)
Recovering Galician historical memory defines the aim of the editorial Ediciós do Castro, without discriminating as regards gender, authors or format. In fact, instead of an editorial line, we could say this is a thread which runs through all collections of Ediciós do Castro, especially when studying the history of the Civil War, repression and exile. This work analyses two collections: “Documents” and “Library of the exile”, and aims to highlight the value of the editorial’s work, despite its disappearance and to make tribute to its creator, Isaac Díaz Pardo.
Keywords: Historical memory; edition; repression; exile; Ediciós do Castro; Isaac Díaz Pardo